TASIC Enterprise - Agus, Muhamad Ali Wahid; Bahari, Mohd Tahir; Anwar, Irmah; Henry, Cherlly Marcella; Muslim, Sazlee Rizuan (2012)
Our company name is TASIC Enterprise. The name of our company represent the name of the partners of our company; (T) Tahir, (A) Ali, (S) Sazlee, (I) Irmah, and (C) Cherlly. Our company is actually involve in the manufacturing industry. In the market, there is no company that sells frozen food like our product, Black Pepper Samosa Chicken. Of course, there many frozen foods like popia, curry puff, "keropok lekor", pau and dumplings, but none has yet to commercialize samosa as frozen food product. Samosa was originated from sub-continent in their for centuries. As introduced by our Prime Minister, Dato' Seri Haji Muhammad Najib Bin Tun Haji Abdul Razak, the "1 Malaysia" concept, we would like to pursue this good will by introducing our product to Malaysian starting with Sabah. It is a healthy food product in the easy and fast way to obtain the nutritious component in the food. Ingredients like black pepper, anise, onions, garlic and chicken contributes to the health beneficial of our product. We categorized our food as "snacks" for its easy to cook and consume points. It can be consumed in anytime of the day, provided it needs to be fried first before consuming. Our reason for choose this business because in Malaysia and specifically in Sabah, samosa is not a familiar snack amongs the local, and we as entrepreneur, grab this opportunity to commercialize samosa to be one of the leading food in the food industry. The nature of the business is partnership. We choose partnership because we have the same goals and we equally responsible for the decision that we make during business. The business will be started with equality contribution. There is a partnership agreement that have been made in order to cover issues like how the profits are divide, the different roles and responsibilities of each partner, the salaries and etc.